EDITORIAL. - Fisher, Jason (Mythprint, 2010)
The author announces his acceptance of a leadership position for "Mythprint," a journal for the Mythopoeic Society. He introduces himself and states that he is a programmer by profession and that he has a wide range of interests which include reading, writing, editing, language, literature and history. As the new editor of "Mythprint," the author hopes to introduce new features, design elements and contents. He also encourages the readers to make suggestions for the newsletter.